Selective extraction of recombinant membrane proteins from Hansenula polymorpha by pulsed electric field and lytic enzyme pretreatment - Valentina Ganeva; Andreas Kranz (Microbial Cell Factories, 2023)
Abstract Background In yeast, recombinant membrane proteins including viral scaffold proteins used for the formation of enveloped Virus-like particles (eVLPs) typically accumulate intracellularly. Their recovery is carried out by mechanical disruption of the cells, often in combination with detergent treatment. Cell permeabilization is an attractive alternative to mechanical lysis because it allows for milder and more selective recovery of different intracellular products. Results Here, we present a novel approach for extraction of integral membrane proteins from yeast based on cell envelope permeabilization through a combination of pulsed electric field and lytic enzyme pretreatment of the cells. Our primary experiments focused on Hansenula polymorpha strain #25-5 co-expressing the integral membrane small surface protein (dS) of the duck hepatitis B virus and a fusion protein of dS with a trimer of a Human papillomavirus (HPV) L2-peptide (3xL2-dS). Irreversible plasma membrane permeabilization was induced by treating the cell suspension with monopolar rectangular pulses using a continuous flow system. The permeabilized cells were incubated with lyticase and dithiothreitol. This treatment increased the cell wall permeability, resulting in the release of over 50% of the soluble host proteins without causing significant cell lysis. The subsequent incubation with Triton X-100 resulted in the solubilization and release of a significant portion of 3xL2-dS and dS from the cells. By applying two steps: (i) brief heating of the cells before detergent treatment, and (ii) incubation of the extracts with KSCN, an 80% purity on the protein level has been achieved. Experiments performed with H. polymorpha strain T#3-3, co-expressing dS and the fusion protein EDIIIWNV-dS consisting of dS and the antigen from the West Nile virus (WSV), confirmed the applicability of this approach for recovering dS. The treatment, optimal for solubilization of 3xL2-dS and a significant part of dS, was not effective in isolating the fused protein EDIIIWNV-dS from the membranes, resulting in its retention within the cells. Conclusions This study presents an alternative approach for the recovery and partial purification of viral membrane proteins expressed in H. polymorpha. The factors influencing the effectiveness of this procedure and its potential use for the recovery of other integral membrane proteins are discussed.